Moda: moderna medida do tempo - Angelica Rodrigues de Oliveira (2011)
This dissertation examines the relationship between fashion and art. More specifically, it aims at understanding fashion as a social phenomenon, originating a new experience of time that modifies its historical narrative. We adopted as theoretical references the works of authors that were sensitive to the transformations of art, time and historical narrative in the beginning of the twentieth century. In our research we have privileged two avant-garde artistic movements: Futurism and Dadaism. As a matter of fact, both understood fashion as an experience of the ephemeral that opened up a new dimension in making art and a new perception of the work of art.